Human health influenced by global warming and mass-media coverage (One Health & Risk Management, 2021)
Introduction. Recently, the issue on global warming and its effects on health has been increasingly debated by the mass-media. Global warming is commonly defined as an increase in Earth's average surface temperature.A crucial role in shaping public opinion and attitude towards this issue is played by the media coverage regarding the climate change. The first long-term studies on the media coverage emerged more than a decade ago, which brought together an international group of researchers. This cooperation was aimed at raising public awareness on the impact of global warming on different life sectors, particularly on human health problems and life effects.Material and methods. This present research was based on the data analysis of media coverage on health issues related to global warming/climate changes. The study assessed 87 articles that have been published over the last 5 years across Moldova, Romania, Russia, France, Germany, and the United Kingdom.Results. Climate changes will always persist, thus, people should take advantage and reduce the risks, by increasing the population’s awareness on this issue. The way media coverage will inform the population depends on the societies that manage this issue. Climate change will become an increasingly important matter for journalists as to provide further open discussions, as well as access to information for a local response to the global problem.As climate change / global warming will steadily occur, people will eventually ask for information regarding that, as well as what they or governments should do upon this problem. Smart and open media managers will consider that opportunity to better inform and serve these audiences.  The major three traditional roles of the media include: raising public awareness, acting as watchdogs; providing social campaigns; maintaining the vital link between scientists and service providers.The journalists commonly consider several things in providing mass-media coverage of health affected by global warming. At the local level, it can save lives, develop action plans, change policy and empower people to take right decisions.Conclusions. Global warming takes one of the decisive roles in shaping the prospects of human development in the 21st century. The informed public understanding of the urgent priority of global warming may create a political space for the government to introduce radical reforms. The media policy should be supplemented by spotlight social messages on TV and Radio formats. A massive public awareness on global warming, its impact on several vulnerable sectors and response measures to adapt to climate change should be carried out by media coverage. Given the effects of climate change and their costs, it can be concluded that mitigation and adaptation would be the best solutions to ensure an on-going human development.
Keywords: global warming; media coverage; public health.